2015
DOI: 10.1093/annhyg/mev023
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Nano-Objects and Their Agglomerates and Aggregates Across Various Life Cycle Stages; A Broad-Scale Exposure Study

Abstract: This broad-scale exposure study gives a comprehensive overview of the NOAA exposure situations in the Netherlands and an indication of the levels of occupational exposure to NOAA across various life cycle of NOAA. The collected workplace exposure data and contextual information will serve as basis for future pooling of data and modelling of worker exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
71
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(71 citation statements)
references
References 37 publications
0
71
0
Order By: Relevance
“…A number of studies demonstrated the potential of occupational exposure to CNTs during activities with CNTs (Maynard et al, 2004;Bello et al, 2008;Han et al, 2008;Yeganeh et al, 2008;Bello, 2009;Tsai et al, 2009;Johnson et al, 2010;Methner et al, 2010;Bello et al, 2010;Lee et al, 2010;Wang and Pui, 2011;Ogura et al, 2011;Dahm et al, 2012;Methner et al, 2012;Takaya et al, 2012;Fleury et al, 2013;Hedmer et al, 2014;Bekker et al, 2015;Dahm et al, 2015). The assessment is complicated as it is difficult to find a sensitive and selective analytical method for CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies demonstrated the potential of occupational exposure to CNTs during activities with CNTs (Maynard et al, 2004;Bello et al, 2008;Han et al, 2008;Yeganeh et al, 2008;Bello, 2009;Tsai et al, 2009;Johnson et al, 2010;Methner et al, 2010;Bello et al, 2010;Lee et al, 2010;Wang and Pui, 2011;Ogura et al, 2011;Dahm et al, 2012;Methner et al, 2012;Takaya et al, 2012;Fleury et al, 2013;Hedmer et al, 2014;Bekker et al, 2015;Dahm et al, 2015). The assessment is complicated as it is difficult to find a sensitive and selective analytical method for CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Downstream activities that may release nanomaterials include bag dumping, manual transfer between processes, mixing or compounding, powder sifting, and machining of parts that contain nanomaterials. Bekker et al summarized the findings of exposure assessments conducted in 15 downstream nanomaterial usage (nonproduction) companies in the Netherlands (Bekker et al 2015). In these companies, across a range of industries, measurements showed that the highest exposure processes included the replacement of intermediate bulk material containers (aka big bags), mixing/dumping of powders, and the spraying of nanomaterial-containing liquids.…”
Section: Introductionmentioning
confidence: 99%
“…As a direct consequence of such quality studies, the amount of available exposure data is increasing rapidly, and therefore, the field is becoming more sophisticated. In 2015, two studies were published that compared numerous sites and sampling events to derive high-confidence conclusions (Bekker et al 2015; Dahm et al 2015); Bekker et al were able to define the highest-exposure task in their study. Such a comprehensive sampling strategy, consistently applied and using a multifaceted methodology, represents the future of occupational nanoparticle exposure assessment.…”
Section: Exposure Assessmentmentioning
confidence: 99%
“…4. Despite these advances, the body of published exposure data focuses extensively on CNTs and TiO 2 and, to a lesser extent, on a few other commercial nanomaterials, such as noble metals (silver), metals and metallic oxides (iron, zinc, aluminum), carbon black, and other carbonaceous materials, such as fullerenes (Bekker et al 2015; Brouwer 2010; Kuhlbusch et al 2011). There remains a need to expand investigations of exposures to other types of ENMs, such as multilayered or functionalized nanoparticles.…”
Section: Exposure Assessmentmentioning
confidence: 99%